A Scenes Approach to Metadata Models for Music. Issue 3 (1st October 2016) - Allison-Cassin, Stacy
Abstract : The underlying conceptual models and assumptions present in works-based bibliographic systems are at odds with the ontological status of music as something that takes place in time. One approach to modeling metadata for music is to use the idea of the music scene. A number of key debates of popular music scenes research are introduced and then two short cases studies are used to demonstrate the challenges and opportunities music presents to the construction of metadata for music, particularly in relation to the idea of music scenes and linked open data. Finally some questions for future work and areas of critique are presented.